2017 American Heart Association Focused Update on Adult Basic Life Support and Cardiopulmonary Resuscitation Quality: An Update to the American Heart Association Guidelines for Cardiopulmonary Resuscitation and Emergency Cardiovascular Care. Issue 1 (2nd January 2018) - Kleinman, Monica E.; Goldberger, Zachary D.; Rea, Thomas; Swor, Robert A.; Bobrow, Bentley J.; Brennan, Erin E.; Terry, Mark; Hemphill, Robin; Gazmuri, Raúl J.; Hazinski, Mary Fran; Travers, Andrew H.
Abstract : Cardiopulmonary resuscitation is a lifesaving technique for victims of sudden cardiac arrest. Despite advances in resuscitation science, basic life support remains a critical factor in determining outcomes. The American Heart Association recommendations for adult basic life support incorporate the most recently published evidence and serve as the basis for education and training for laypeople and healthcare providers who perform cardiopulmonary resuscitation.